The Determinants of Biodiesel Export in Indonesia - Andika Pambudi; Eka Puspitawati; Nursechafia Nursechafia (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2019)
This study investigates the competitiveness of Indonesian biodiesel export among the top seven of biodiesel trader countries in the world, as well as the factors that determine export for Indonesian biodiesel. Applying Revealed Comparative Advantage (RCA) analysis, the results show that Indonesia has good competitiveness of biodiesel in the world. Using secondary data, the results of the gravity model indicate that distance of trade destination countries harms the Indonesian biodiesel export. Meanwhile, price, exchange rate, and GDP have a positive effect on the export. Based on the results of this study, the government of Indonesia should focus on the development of the biodiesel industry, since the increasing importance of biodiesel as alternative energy in the world